The Role of Cost Management Accounting in Supporting Sustainable Development in Vietnamese Enterprises - Luong Minh Hang (Westscience Press, 2024)
This study was conducted to examine the role of cost management accounting in supporting sustainable development in Vietnamese enterprises. This study attempts to understand how cost management accounting can contribute to sustainable development in Vietnamese companies, including identifying and quantifying environmental and social impacts, improving efficiency and reducing costs, and supporting the development of sustainable development initiatives. The study identifies challenges and barriers in implementing cost management accounting to support sustainable development in Vietnamese companies, including lack of awareness and understanding, lack of standardization and lack of stakeholder engagement. The study builds a framework for integrating cost management accounting with sustainability initiatives at Vietnamese companies, including key components such as defining sustainable development, identifying and measuring environmental and social impacts, quantifying financial impacts, and promoting transparency and accountability. The findings and research framework can be used to support the development of sustainable development initiatives in Vietnamese companies, contributing to the implementation of the country's sustainable development goals and improving the competitiveness and reputation of Vietnamese enterprises.